Implementasi Model Problem Based Learning Berbantuan Media Genially Untuk Menumbuhkan Motivasi Siswa Pada Pembelajaran Pendidikan Pancasila Dikelas II SDN 04 Palembang - A. Aunur Rhofiqoh. R; Kiki Aryaningrum; Budi Utomo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of student learning motivation in Pancasila Education learning, and the fact that students are still less active, less focused, and less enthusiastic during the learning process. Therefore, it is necessary to apply innovative learning models and media to foster student learning motivation. This study aims to describe the implementation of the Problem Based Learning model assisted by Genially media to foster student learning motivation in Pancasila Education learning in class II of SDN 04 Palembang. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, questionnaires, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the data analysis show that the application of the Problem Based Learning model assisted by Genially media is able to foster student learning motivation obtained by the percentage of the questionnaire on the indicator of feelings of pleasure of 92%, student attention of 100%, interest in learning of 100%, and student involvement in learning of 96% with a very good category. In addition, students appear more active, enthusiastic, and eager to participate in learning. Thus, the application of the Problem Based Learning model assisted by Genially media can foster students' learning motivation in Pancasila Education learning in class II of SDN 04 Palembang.